4
$\begingroup$

Let, $\alpha_2=\frac{a+1}{a}, \alpha_1^k =(\frac{xz}{y^2})^k \leq \frac{1}{b}$, then, $$\varLambda := \log\alpha_2- k\log\alpha_1$$

In the paper linear forms in the logarithms of real algebraic numbers close to 1, it is written on page $9$ that

On other hand, a short calculation yields $$ \left|\frac{a+1}{a}- \left(\frac{xz}{y^2}\right)^k\right|\leq \frac{1}{b} \quad (13)$$ thus, we have, $$ \log\varLambda \leq - \frac{log(b)}{12}$$

we see there is a $12$ as denominator!! , the claim is- $$\log (\log\alpha_2- k\log\alpha_1) \leq - \frac{log(b)}{12}$$

$$ \implies \log\varLambda \leq - \frac{log(b)}{12}$$.

Why $-\log b$ is divided by $12$?

So, how do we derive, $\log\varLambda \leq - \frac{log(b)}{12}$ from $ \left|\frac{a+1}{a}- \left(\frac{xz}{y^2}\right)^k\right|\leq \frac{1}{b}$ ?

Image of the page :-

enter image description here enter image description here

$\endgroup$
1
+50
$\begingroup$

We have $$(a+1)(ab^2+1)\gt (ab+1)^2$$ and so $$b(a+1)(ab^2+1)\gt b^{1/12}(ab+1)^2$$ from which $$\alpha_1^k=\frac{(a+1)(ab^2+1)}{(ab+1)^2}\gt b^{-11/12}\tag{*1}$$ follows.

By the mean value theorem, there exists a real number $c$ such that $$\frac{\log{\alpha_2}-\log{\alpha_1^k}}{\alpha_2-\alpha_1^k}=\frac 1c\qquad\text{and}\qquad \alpha_1^k\lt c\lt\alpha_2\tag{*2}$$ from which $$\alpha_2-\alpha_1^k=c(\log{\alpha_2}-\log{\alpha_1^k})=c\varLambda $$ follows.

It follows that $$\begin{align}\log\varLambda&=\log\left(\frac{\alpha_2-\alpha_1^k}{c}\right) \\\\&=\log(\alpha_2-\alpha_1^k)-\log c \\\\&\lt \log\frac 1b-\log{\alpha_1^k}\qquad\qquad (\text{from $(13)$ in the paper and $(*2)$}) \\\\&\lt -\log b-\log{b^{-11/12}}\qquad\qquad(\text{from $(*1)$}) \\\\&=-\frac{\log b}{12}\end{align}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.